Perlindungan Hukum oleh Pemerintah terhadap Perkawinan Masyarakat Adat: Studi Kasus Suku Samin di Kabupaten Kudus - Mujahidin, Imamul Mujahidin (Tebuireng: Journal of Islamic Studies and Society, 2023)
The traditional marriage of the Samin tribe in Kudus Regency shows that there are marriages that cannot be registered with the Population Administration. The researcher found that the Samin tribe in Kudus Regency could not register their marriage, thus preventing them from obtaining civil rights. The main reason is that the religious identity on the KTP is written in Islam even though basically they are not Muslims. This study aims to identify the factors that influence the reluctance of the Samin people to register marriages and the village government's efforts to legalize Samin people's customary marriages in the form of registering marriages without involving state officials. This research is a qualitative field research and the data were obtained systematically directly from the field. This research descriptively examines observation data, interview results, and documents. After a thorough examination, it can be concluded that the Samin tribal marriage custom is not considered legally binding in Indonesia because it does not involve a marriage registrar. However, the decision of the Constitutional Court which is identified with Number 97/PUU-XIV/2016 has provided a glimmer of hope for the Indonesian nation by allowing the inclusion of "Belief in the One and Only God" in the KTP religion column. This decision has allowed the Samin tribe to legally register their marriages with the registry, according to their customs.